2015
DOI: 10.1017/s0031182015000190
|View full text |Cite
|
Sign up to set email alerts
|

Development of a strategy for the identification of surface proteins in the pathogenic microsporidianNosema bombycis

Abstract: Parasite-host interactions mediated by cell surface proteins have been implicated as a critical step in infections caused by the microsporidian Nosema bombycis. Such cell surface proteins are considered as promising diagnostic markers and targets for drug development. However, little research has specifically addressed surface proteome identification in microsporidia due to technical barriers. Here, a combined strategy was developed to separate and identify the surface proteins of N. bombycis. Briefly, followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…A number of spore wall proteins (SWPs) have been identified and confirmed to be related to germination and invasion (Zhao W. et al, 2015 ). SWP5 has been confirmed to have the ability to protect spores from phagocytic uptake by cultured insect cells to modulate host cell invasion and interact with the polar tube (Cai et al, 2011 ; Li et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of spore wall proteins (SWPs) have been identified and confirmed to be related to germination and invasion (Zhao W. et al, 2015 ). SWP5 has been confirmed to have the ability to protect spores from phagocytic uptake by cultured insect cells to modulate host cell invasion and interact with the polar tube (Cai et al, 2011 ; Li et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear how accurate these approaches are at identifying such proteins in microsporidia and these prediction methods do not distinguish between proteins partially or wholly outside the microsporidia cell from those directed to internal membranes or compartments13. Although some host-exposed microsporidia proteins have been characterized23242526272829, no comprehensive identification of such proteins has been carried that include the intracellular stage of the pathogen.…”
mentioning
confidence: 99%
“…; Zhao et al. ). Here, with the help of bioinformatic analysis, we captured 83 candidate spore wall proteins in N. bombycis , including the previously identified spore wall proteins NbSWP5, NbSWP16 and the protein EOB13320 of this microsporidia (Cai et al.…”
Section: Discussionmentioning
confidence: 98%
“…An increasing number of evidence indicated that microsporidian spore wall proteins play key roles in the pathogen-host interaction process, such as the pathogen infection, invasion and other pathogenic process (Weidner 1992;Weidner and Halonen 1993). However, to discover the underlying mechanism of parasite-host interaction in microsporidia, the number of the characterized spore wall proteins are still much less today, though a few proteins had been identified in last decades (Bohne et al 2000;Hayman et al 2001;Southern et al 2007;Wu et al 2008;Zhao et al 2015). Here, with the help of bioinformatic analysis, we captured 83 candidate spore wall proteins in N. bombycis, including the previously identified spore wall proteins NbSWP5, NbSWP16 and the protein EOB13320 of this microsporidia (Cai et al 2011;Li et al 2012Li et al , 2015Wang et al 2015).…”
Section: Discussionmentioning
confidence: 99%